The Disruptive Search for Identity - Han, Fook Kwang (2017)
The world is entering a new period of political uncertainty amid a popular backlash against globalisation. People feel dislocated in their own societies and want to reclaim their identity. This search for identity is what causes many conflicts and will make for a more disruptive future.